(untitled) (Universal International Scientific Journal, 2026)
This article examines the psychological aspects of the process of adaptation of women in military families to a new socio-environment. The main factors influencing women’s adaptation, including stress and anxiety management strategies, the role of social support systems, and the effectiveness of special psychological programs, are analyzed in detail.